CHILDREN’S STORIES: REALITY AND CULTIVATION - Tiara Sevi Nurmanita (Fakultas Sastra Universitas Negeri Malang, 2020)
CHILDREN’S STORIES: REALITY AND CULTIVATION Abstract: The purpose of this study is to examine the reality and cultivation of children's stories by children and adults. Children's stories used in this study are children's novels. The method used is literary analysis in the form of a mimetic approach. Data sources are in the form of text excerpts from children's novels by children and adults. The results of the study are a comparison of reality and story development in children's novels by children and adults. In terms of reality, it is found that children's stories are imitations of children's real life interpretations as reviewed in children's characteristics. When viewed from the perspective of cultivation, children's stories written by children have simpler storyline, use many conversational texts and tend to use simple sentences. On the other hand, the storylines and sentences in children's stories written by adults are more complex, although the vocabulary used is still simple.Keywords: Children's stories, Reality, StorylinesCERITA ANAK: REALITAS DAN PENGGARAPANAbstrak: Tujuan artikel ini mengkaji realitas dan penggarapan pada cerita anak karya anak-anak dan orang dewasa. Cerita anak yang digunakan yakni novel anak. Metode kajian menggunakan analisis sastra berupa pendekatan mimetik. Sumber data berupa kutipan teks dari novel anak karya anak-anak dan orang dewasa. Hasil penelitian berupa perbandingan realitas dan penggarapan cerita pada novel anak karya anak-anak dan orang dewasa. Segi realitas ditemukan bahwa cerita anak merupakan tiruan interpretasi kehidupan nyata anak, ditinjau dari karakteristik anak-anak. Ketika dilihat dari sudut pandang penggarapan, cerita anak yang ditulis oleh anak-anak memiliki alur cerita lebih sederhana, banyak menggunakan teks percakapan dan cenderung menggunakan kalimat sederhana. Untuk cerita anak yang ditulis orang dewasa memiliki alur cerita dan kalimat lebih kompleks meskipun kosakata yang digunakan masih sederhana.Kata kunci: Cerita anak, Realitas, Alur cerita